Measuring. Monitoring. Management. Control - P.G. Mikhaylov; A.P. Mikhaylov; I.N. Paskhin; A.R. Akhmetov; E.D. Fadeev (Измерение, мониторинг, управление, контроль)
Background. The article is devoted to the development of constructive and technological methods for ensuring the temporal and parametric stability of films and film structures formed on metal–film sensors of physical quantities. The relevance of the presented materials lies in the fact that the stability of sensors depends to a greater extent on the stability of resistive films and film structures. The purpose of the article is to develop reproducible designs and technologies that ensure the formation of time-stable sensor elements and structures. Materials and methods. The article describes in sufficient detail the proposed designs of polyfilm strain-resistant structures of various configurations. Mathematical models of multilayer film structures are considered and analyzed, the nominal values of strain gages are determined, and methodformation are determined. In particular, an increase in the accuracy and consistency of the electrophysical characteristics of the sensing elements and measuring modules was achieved by 30–40 % compared with well-known Russian sensors.s for minimizing the temperature coefficients of resistive structures are determined. Results and conclusions. As a result of the research conducted in the field of developing methods for regulating and maintaining the temporal and parametric stability of sensor characteristics, the designs of polyfilm structures and methods of their